Sosialisasi Pembebasan Bersyarat pada Narapidana di Lembaga Pemasyarakatan Kelas IIA Watampone - Andi Hartawati; Elvi Susanti Syam; Sumiati Beddu (Journal of Community Service and Engagement, 2026)
The purpose of this community service is to disseminate information on the implementation of parole in accordance with Law Number 22 of 2022 to prisoners, and to identify the supporting and inhibiting factors at the Watampone Class IIA Prison. This dissemination uses the lecture method to all inmates and correctional officers, followed by a question and answer session and the distribution of questionnaires, which are then analyzed juridically and empirically using a qualitative approach, utilizing primary and secondary data. Primary data was obtained through interviews with officials and correctional officers, as well as questionnaires given to inmates who were recipients or potential recipients of parole. Secondary data was sourced from laws and regulations, literature, and official prison documents. The results of the socialization show that the implementation of parole at the Watampone Class IIA Prison for the 2021–2024 period has been optimal, with an increasing trend in the number of recipients each month and a 90% success rate in completing the probation period without violations. Supporting factors include the commitment of officers, clear regulations, an integrated data system, and service innovations. Hindering factors include limited human resources, administrative constraints, minimal infrastructure, community stigma, unknown whereabouts of family guarantors, and disciplinary violations by prisoners that result in failure to obtain parole..